Improving diversity in study participation: Patient perspectives on barriers, racial differences and the role of communities - Lisa Shea; Jacqueline Pesa; Gabrielle Geonnotti; Valerie Powell; Caryl Kahn; Wesley Peters (Wiley, 2022)
Abstract Introduction The lack of racial/ethnic diversity in research potentially limits the generalizability of findings to a broader population, highlighting the need for greater diversity and inclusion in clinical research. Qualitative research (i.e., focus groups) was conducted to identify (i) the potential motivators and barriers to study participation across different races and ethnicities; (ii) preferred delivery of education and information to support healthcare decision‐making and the role of the community. Methods Patient focus groups were conducted with 26 participants from the sponsor's Patient Engagement Research Councils selected through subjective sampling. Recruitment prioritized adequate representation across different race/ethnic groups. Participation was voluntary and participants underwent a confidential interview process before selection. Narrative analysis was used to identify themes and draw insights from interactions. Experienced research specialists identified emerging concepts, and these were tested against new observations. The frequency of each concept was examined to understand its importance. Results Based on self‐selected race/ethnicity, participants were divided into five focus groups (Groups: African American/Black: 2; Hispanic/Latino, Asian American, and white: 1 each) and were asked to share their experiences/opinions regarding the stated objectives. Barriers to study participation included: limited awareness of opportunities to participate in research, fears about changes in standard therapy, breaking cultural norms/stigma, religion‐related concerns and mistrust of clinical research. Participants identified the importance of transparency by pharmaceutical companies and other entities to build trust and partnership and cited key roles that communities can play. The perceptions of the African American group regarding diversity/inclusion in research studies appeared to be different from other groups; a lack of trust in healthcare providers, concerns about historical instances of research abuse and the importance of prayer were cited. Conclusion This study provided insights into barriers to study participation, and also highlighted the need for pharmaceutical companies and other entities to authentically engage in strategies that build trust within communities to enhance recruitment among diverse populations. Patient or Public Contribution The data collected in the present study was provided by the participants in the focus groups.